Bi-directional in sustainability reporting and profitability: A study in Indonesian banks and non-banks - Tri Gunarsih; Setiyono Setiyono; Fran Sayekti; Tamas Novak (Jurnal Keuangan dan Perbankan, 2020)
We investigate the sustainability reporting differences in banks and non-banks sample firms and investigates reserve causality between sustainability reporting and profitability. The independent-sample t-test implemented to analyze the differences. The results report evidence that there are differences in sustainability reporting between the banks and non-bank. The average score of the sustainability reporting index in banks is higher than non-bank. The multiple regressions implemented in reserve causality between sustainability reporting and profitability. The empirical evidence shows that there is a negative relationship between sustainability reporting and profitability. We suggest that sustainability is merely a cost. The bi-directional relationship emerges in the economic and social dimension of sustainability reporting index. This result indicates that sustainability reporting influences firm performance and vice versa.JEL Classification: G21, G30 How to Cite:Gunarsih, T., Setiyono, Sayekti, F., Novak, T. (2020). Bi-directional insustainability reporting and profitability: A study in Indonesian banks and non-banks. Jurnal Keuangan dan Perbankan, 24(1), 20-29.DOI: https://doi.org/10.26905/jkdp.v24i1.3588